Correction: The stability and generation pattern of thermally formed isocyanic acid (ICA) in air – potential and limitations of proton transfer reaction-mass spectrometry (PTR-MS) for real-time workroom atmosphere measurements. Issue 2 (7th February 2018) - Jankowski, Mikolaj Jan; Olsen, Raymond; Thomassen, Yngvar; Molander, Paal
Abstract : Correction for 'The stability and generation pattern of thermally formed isocyanic acid (ICA) in air – potential and limitations of proton transfer reaction-mass spectrometry (PTR-MS) for real-time workroom atmosphere measurements' by Mikolaj Jan Jankowski et al., Environ. Sci.: Processes Impacts, 2016, 18, 810–818.